Ablasio Retina Rhematogen pada Pria Usia Lanjut dengan Riwayat Katarak : Laporan Kasus - Cut Aja Nurul Huzaifah; Cut Balqis Ammara; Fauzan Teuku Banta (STIKES Columbia Asia Medan, 2025)
Rhegmatogenous retinal detachment is a condition in which the sensory retina separates from the retinal pigment epithelium due to a retinal tear that allows vitreous fluid to accumulate in the subretinal space. It is an ophthalmologic emergency that may result in permanent blindness if not managed promptly and appropriately. This case report aims to describe the clinical course, diagnosis, and management of a 62-year-old male patient who presented with sudden blurred vision in the right eye, accompanied by floaters, photopsia, and discomfort. The patient had a history of bilateral cataracts and underwent vitrectomy. Data were collected from medical records and supporting examinations, confirming the diagnosis of rhegmatogenous retinal detachment. Management included topical therapy, systemic medication, bed rest, and surgical intervention. Clinical improvement was observed postoperatively. This report highlights the importance of early detection and timely treatment to preserve visual function.